A PICTURE PAINTS A THOUSAND WORDS: A PHENOMENOLOGICAL STUDY OF MISCONCEPTIONS OF GRADE 7 MATHEMATICS TEACHERS ON DIFFERENTIATED INSTRUCTION IN THE PHILIPPINES - Castillo-Magayon, Victoria; Beyaoju Tan, Emily (PEOPLE: International Journal of Social Sciences, 2018)
Differentiated Instruction has been found to be effective in catering to the individuality of students and at the same time helping students to have positive attitudes about school, increased engagement in learning, and improved achievement. Misconceptions of this type of instruction limit the teachers’ response to student conceptions and ability to create challenging learning situations. For these reasons, researches on this topic are highly needed, especially in the Philippines, wherein, content differentiation is suggested in the implementation of the K-12 curriculum program, hence this study aimed to surface the misconceptions of Grade 7 mathematics teachers on differentiated instruction through the research question: What are the misconceptions of Grade 7 Filipino mathematics teachers on Differentiated Instruction? Data from the interviews of 21 Grade 7 Filipino mathematics teachers are qualitatively described through this phenomenological study which utilizes the Colaizzi’s Method to analyze data. The findings of this study surfaced the Grade 7 mathematics teachers’ misconceptions on DI in the Philippines as fragmented ideas, and tagged them as head, heart, life, hand, road, and gadget. Fragmented because the respondents did not give the complete picture of DI but rather they provided characteristics of other teaching approaches related to DI. The findings are not surprising since DI came from the constructivist view, but DI has unique features and characteristics, and outside of these are all misconceptions. Hence, the respondents’ notions of DI are as, “a picture paints a thousand words.” Future researches are suggested out of the findings of this study such as “Determining the Effects of Relating Real Life Situations in Teaching Mathematics Lessons Utilizing DI” and “Challenges Encountered by Mathematics Teachers in Applying DI in Basic Education Institutions in Asia.”